Industry needs in Requirements Engineering: XXI century challenges for an IT curricula - Brito, Isabel S.; Pinto-Albuquerque, M.; Barreiros, Jorge; Cruz, António Miguel Rosado da (3rd International Conference of the Portuguese Society for Engineering Education (CISPEE 2018), 2018)
The Requirements Engineering (RE) community must be prepared for XXI century challenges, such as Industry 4.0. Considering this, we collect the requirements engineering needs and challenges indicated by ten enterprises that operate in the Portuguese information technology (IT) market. We aim to bring to the wider IT academic community, awareness of the challenges the industry is confronted with in the area of RE, to inform IT engineering curricula, and foster industry-academia cooperation. These needs and challenges were collected in a workshop (http://re2017.org/pages/conference/rept/) that brought together academia and industry members of the Portuguese community.